2018
DOI: 10.1080/15592324.2017.1422461
|View full text |Cite
|
Sign up to set email alerts
|

Floral fragrance analysis of Prosthechea cochleata (Orchidaceae), an endangered native, epiphytic orchid, in Florida

Abstract: South Florida is home to a number of native species of orchids. The Florida Panther National Wildlife Refuge has 27 known species, including Prosthechea cochleata, the clamshell orchid, which is listed as endangered on Florida's Regulated Plant Index. In a prior study done on this species in Mexico, P. cochleata was found to produce no floral fragrance at the particular study location. However, blooming orchids of this species at the University of Florida in Gainesville, were noted to be fragrant. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Disa pulchra does not provide a nectar reward for its fly pollinators, possibly causing flies to visit fewer flowers on the same plant and increasing the likelihood of self-pollination. Ray et al (2018) examined the floral fragrance of this orchid species and found that it was producing volatiles similar to those found in other orchid fragrance studies. This suggests that it is producing a fragrance in order to attract a pollinator.…”
Section: Discussionsupporting
confidence: 60%
“…Disa pulchra does not provide a nectar reward for its fly pollinators, possibly causing flies to visit fewer flowers on the same plant and increasing the likelihood of self-pollination. Ray et al (2018) examined the floral fragrance of this orchid species and found that it was producing volatiles similar to those found in other orchid fragrance studies. This suggests that it is producing a fragrance in order to attract a pollinator.…”
Section: Discussionsupporting
confidence: 60%
“…Like many plants, orchids often secrete fragrances involved in pollinator attraction (Knudsen et al 1993;Brown 2005;Dudareva & Pichersky 2006). Fragrance emission rate can differ over a 24 h period, as well as across locations, which can lead to difficulty in determining the floral volatiles for each species (Ray et al 2018;Ray et al 2019). Floral volatiles are very complex and while they may be used to advertise a nectar reward, they often mimic natural odours that are very specific attractants for different species.…”
Section: Orchid Floral Fragrancementioning
confidence: 99%
“…The cockleshell orchid, also known as the clamshell orchid, has pseudo bulbs that look like hoods growing from the plant, from which the flower blooms.It is native to Central America, the West Indies, Colombia, Venezuela, and southern Florida and is the national flower of Belize, where it is also known as the black orchid [11] (Figure .11). It is originally from the southern part of South America (Fig.…”
Section: Cockleshell Orchid (Prosthechea Cochleata)mentioning
confidence: 99%